LEGAL PROTECTION OF GEOGRAPHICAL INDICATIONS FOR TAMARENJA SNAKEFRUIT: IMPLICATIONS FOR THE LOCAL COMMUNITY’S ECONOMY - Maulana Amin Tahir; Mohammad Saleh (Program Studi Hukum Ekonomi Syariah, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2025)
Geographical Indication is a term that indicates the area of origin of a good or product. This uniqueness is caused by unique environmental factors, including natural and human influences, contributing to the goods and products' reputation, quality, and characteristics. Registered Geographical Indications can be a valuable asset that supports the regional economy. One of the regional products that can potentially obtain Geographical Indication protection is Tamarenja Snakefruit from Tamarenja Village, Donggala Regency, Central Sulawesi Province. This study aims to examine the potential for legal protection of Geographical Indication Rights for Tamarenja Snakefruit and to examine the efforts of the Tamarenja Village Government and Community in registering Tamarenja Snakefruit as a Geographical Indication product. This study uses a descriptive qualitative research approach with an empirical legal research type, which involves collecting primary data through direct interviews with informants and document searches. The results of the study indicate that Tamarenja Snakefruit has the potential to be registered as a Geographical Indication product at the Ministry of Law and Human Rights of the Republic of Indonesia. Therefore, the involvement and efforts of the Tamarenja Village Government are significant in facilitating the registration process to improve the local economy. The Donggala Regency dan Tamarenja Village Government has made various efforts to register Tamarenja Snakefruit as a Geographical Indication product, including by conducting outreach to snakefruit farmers regarding the importance of registering geographical indications as a form of legal protection for intellectual property rights and as an instrument for improving the economy of snakefruit farmers. Abstrak Indikasi Geografis merupakan sebutan yang menunjukkan daerah asal suatu barang atau produk. Keistimewaan ini disebabkan oleh faktor lingkungan yang unik, termasuk pengaruh alam dan manusia, yang berkontribusi terhadap reputasi, kualitas, dan karakteristik barang dan produk. Indikasi Geografis yang terdaftar dapat menjadi aset berharga yang mendukung perekonomian daerah. Salah satu produk daerah yang berpotensi untuk mendapatkan perlindungan Indikasi Geografis adalah Buah Snakefruit Tamarenja yang berasal dari Desa Tamarenja, Kabupaten Donggala, Provinsi Sulawesi Tengah. Tujuan penelitian ini adalah untuk mengkaji potensi perlindungan hukum Hak Indikasi Geografis bagi Buah Salak Tamarenja dan untuk mengkaji upaya Pemerintah dan Masyarakat Desa Tamarenja dalam mendaftarkan Buah Salak Tamarenja sebagai produk Indikasi Geografis. Penelitian ini menggunakan pendekatan penelitian kualitatif deskriptif dengan jenis penelitian hukum empiris, yang melibatkan pengumpulan data primer melalui wawancara langsung dengan narasumber dan penelusuran dokumen. Hasil penelitian menunjukkan bahwa Buah Salak Tamarenja berpotensi untuk didaftarkan sebagai produk Indikasi Geografis di Kementerian Hukum dan Hak Asasi Manusia Republik Indonesia. Oleh karena itu, keterlibatan dan upaya Pemerintah Desa Tamarenja sangat penting dalam memfasilitasi proses pendaftaran untuk meningkatkan perekonomian setempat. Pemerintah Kabupaten Donggala dan Desa Tamarenja telah melakukan berbagai upaya dalam mendaftarkan Buah Snakefruit Tamarenja sebagai produk Indikasi Geografis diantaranya dengan melakukan sosialisasi kepada para petani buah salak akan pentingnya pendaftaran indikasi geografis sebagai bentuk perlindungan hukum hak kekayaan intelektual dan merupakan salah satu instrumen peningkatan ekonomi para petani buah snakefruit